MARMARONIA ANGIOLINII, NEW GENUS AND NEW SPECIES OF BAKEVELLIIDAE (PTERIOIDA, BIVALVIA) FROM THE MIDDLE PERMIAN OF CHIOS (GREECE) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
The Guadalupian (Middle Permian) "Gymnocodiacean Limestones" cropping out in the north-eastern part of the Greek island of Chios (eastern Aegean Sea) are amongst the most fossiliferous in the western Tethys. They contain rich assemblages of corals, brachiopods, molluscs, calcareous algae, foraminifers and ostracods. Scant attention was given till now to mollusc faunas compared with brachiopods and foraminifers. In the present paper the new genus Marmaronia, with type-species M. angiolinii n. sp., is established to distinguish some bivalves of the Bakevelliidae King, 1850, from the middle Guadalupian successions of the Marmaro locality in Chios Island. M. angiolinii n. gen. n. sp. is strongly inequivalve, with valves differing in convexity, umbo development and ornamentation. The left valve shows a radial furrow running from the anterior part of the umbonal region anteroventrally and is ornamented by strong radial costae; the right valve is ornamented by concentric sculpture and by thin rugae in the first growth stages of the posterior part of the shell. Both valves have a wide posterior wing. Two hypotheses concerning the epi- or endobyssate adaptation of Marmaronia are also discussed briefly in the present paper.